Heme-copper and heme-heme interactions in the cytochrome bo-containing quinol oxidase of Escherichia coli. - J.C. Salerno; Barbara Bolgiano; Robert K. Poole; Robert B. Gennis; W. John Ingledew (1990)
The cytochrome bo quinol oxidase of Escherichia coli is one of two respiratory O2 reductases which the bacterium synthesizes. The enzyme complex contains copper and 2 mol of b-type heme. Electron paramagnetic resonance (epr) spectroscopy of membranes from a strain having amplified levels of this enzyme complex reveals signals from low- and high-spin b-type hemes, but the copper, now established as a component of the oxidase, is not directly detectable by epr. The high-spin signal from the cytochrome bo complex, which we attribute to cytochrome o, when titrated potentiometrically, gives a bell-shaped curve. The low potential side of this curve is biphasic (Em7 approximately 180 and 280 mV) and corresponds to the reduction/oxidation of the cytochrome(s). The high potential side of the bell-shaped curve is monophasic (Em7 approximately 370 mV) and is proposed to be due to reduction/oxidation of a copper center which, when in the Cu(II) form, is tightly spin-coupled to a heme, probably cytochrome o, resulting in a net even spin system and loss of the epr spectrum. The low-spin cytochrome b titrates biphasically with Em7 values of approximately 180 and 280 mV, similar to the high-spin component but without the loss of signal at high potentials.